Trade Cost Reduction and Foreign Direct Investment in a Vertical Structure - M. Emranul Haque; Arijit Mukherjee; Burcu Senalp (Center for Economic Studies and ifo Institute (CESifo), 2017)
Although empirical evidence shows that a lower trade cost and higher FDI may go hand in hand, the well-known “proximity-concentration” hypothesis does not support this view. We provide a simple explanation for this phenomenon. We show that a lower trade cost on the intermediate goods (with or without a trade cost reduction on the final goods) increases the incentive for FDI in the final goods market. In this respect, we show the roles played by the production technologies of the firms.
Keywords: 330